Ernest saves Christmas - Varney, Jim.; Clark, Oliver; Parker, Noelle; Sartain, Gailard; Bird, Billie; Byrge, Bill.; Seale, Douglas, 1913-1999.; Cherry, John; Turner, Ed, 1935-; Touchstone Pictures; Silver Screen Partners III.; Emshell Producers Group Production Home Video (Firm); et al. (Burbank, Calif. : Touchstone Home Video : Distributed by Buena Vista Entertainment, 2002)
When Santa Claus decides to retire and pass on his magic bag of Christmas surprises to a new St. Nick, he enlists the aid of a hilarious assortment of characters, including Ernest P. Worrell (Jim Varney).
Originally released as a motion picture in 1988.
Jim Varney, Oliver Clark, Noelle Parker, Gailard Sartain, Billie Bird, Bill Byrge and Douglas Seale.
DVD; widescreen, Dolby Digital stereo.
Keywords: Santa Claus; Retirement; DVD-Video discs; Comedy films; Feature films; Christmas films; Video recordings for the hearing impaired